The Income Comparison of Broiler Farming that Used Closed House System and Open House System - Sari, Ida Ayu Putri Lingga; Susrusa, Ketut Budi; Listia Dewi, Ida Ayu (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 2 (2021): Vol.15, No.2, 2021DO - 10.24843/SOCA.2021.v15.i02.p12, 2021)
One of the important elements in a broiler farming business was the cage. The types of broiler chicken cages based on the type of the wall can be divided into closed house cages and open house cages. This research was conducted on farmers who partnered with UD Bagus Ternak with the aim of knowing the comparison of costs, FCR, production, and income of broiler farming that used a closed house system and an open house system. The selection of location was done intentionally and the respondents were selected by census, which was five farmers that used the closed house system and 22 farmers use the open house system. The results showed that the costs and income of broiler farming that used a closed house system were Rp. 224,615,108/500m2 and Rp. 17,301,892/500m2, while the costs and income of broiler farming that used an open house system were Rp. 126,478,036/500m2 and Rp.5,146,964/500m2. The results of the Mann-Whitney test on the average cost and income of the two broiler farm cage systems, statistically were significantly different. The FCR of broiler farming that used the closed house system (1.62) was less than the open house system (1.73) and statistically, significantly different. The results of broiler farm production that used the closed house system (1.86kg/head) were greater than the open house system (1.82kg/head) and statistically there was no difference.